Color image encryption based on finger vein key and off-axis digital holography with phase-modulated reference light - Boyu Wang; Yanfeng Su; Ming Gao; Hong Lyu; Jiayin Zhang; Bei Zhou; Wenqi Zhong; Peng Zhang; Yinghong Li (Scientific Reports)
Abstract In this paper, a color image encryption method based on finger vein key and off-axis digital holography with phase-modulated reference light is proposed. In the encryption process, firstly the channel separation operation is performed on the color plaintext image, and the “red”, “green” and “blue” channels grayscale data of the color plaintext image are obtained respectively. Subsequently, the finger vein quantum matrix of the encryption user is generated through the quantum matrix generation program and used as the scrambling index key, mask key, and phase mask keys in the next encryption steps. The grayscale data of each channel of the original color plaintext image is then encrypted using the DNA coding encryption operation, and these encrypted results are embedded into the carrier image, thus the encryption watermark image is obtained. After, the encryption watermark image is executed image encryption operation based on double random phase coding (DRPE) in the Fresnel transform domain, so that the encryption object light is obtained. Finally, the off-axis digital holography encoding technology (ODHE) with phase-modulated reference light is performed on encryption object light, so that the finally holographic ciphertext is generated. In the decryption process, the decryption user’s finger vein must first be authenticated. If the authentication is successful, the system proceeds with the subsequent decryption steps, so that the correct decrypted color image can be obtained; otherwise, the decryption process is terminated. In order to demonstrate the feasibility of the proposed color image encryption method, a series of numerical simulations are performed, and the simulation results show that the proposed method exhibits high feasibility as well as high security level, large key space, contactless authentication, strong portability of ciphertext, strong robustness and security of finger vein key.